Method for regulating and controlling stress corrosion cracking of microorganisms
By constructing a multi-level biofilm adhesion area gradient and stress concentration zone on a U-shaped metal sample, and combining finite element analysis and electrochemical testing, the problem of the lack of a quantitative correlation experimental framework in the existing technology was solved. This enabled precise control and quantitative analysis of microbial stress corrosion cracking, providing a direct theoretical basis for protection strategies.
Patent Information
- Application Number
- CN202511670928.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-02-03
AI Technical Summary
Existing technologies lack an experimental framework that quantitatively correlates biofilm adhesion area, stress concentration zone, and corrosion mechanism, resulting in a lack of precise design basis for protective measures against microbial stress corrosion cracking.
By preparing U-shaped metal samples, the stress concentration zone was calibrated using the finite element method, a multi-level biofilm adhesion area gradient was constructed, constant tensile stress was applied and the samples were cultured in an anaerobic environment, corrosion indicators were detected periodically, and a quantitative relationship between biofilm adhesion area and corrosion rate and crack propagation depth was established by combining scanning electron microscopy and X-ray photoelectron spectroscopy analysis.
This study achieved precise control and quantitative analysis of microbial stress corrosion cracking behavior, revealed the regulatory law of biofilm spatial distribution on crack initiation and propagation, and provided prediction and targeted protection strategies for material failure risk.
Smart Images

Figure CN121453636A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of material corrosion, and particularly relates to a method for regulating microbial stress corrosion cracking. BACKGROUND
[0002] Microbiologically Influuced Stress Corrosion Cracking (MISCC) is one of the main failure modes of high-strength steel components such as oil and gas pipelines, marine structures and underground storage tanks under the combined action of tensile stress and microbial corrosion. Among them, sulfate-reducing bacteria (SRB) is considered to be the core microbial population inducing MISCC because it produces hydrogen sulfide (H2S) through anaerobic metabolism and can directly uptake metal electrons through extracellular electron transfer (EET). Traditional researches have focused on the influence of single bacterial amount or metabolic product concentration on crack initiation, ignoring the regulation effect of biofilm spatial distribution on local electrochemical microenvironment and stress-corrosion coupling effect. In recent years, finite element stress analysis and micro-area electrochemical testing have been gradually applied to MISCC research, but there is still a lack of experimental framework for quantitatively correlating the three of “biofilm attachment area-stress concentration area-corrosion mechanism”, resulting in the lack of precise design basis for area-mechanism coupling of on-site protection measures (coating, cathodic protection, bactericide).
[0003] Therefore, it is urgent to establish a new experimental method that can directionally regulate biofilm distribution, synchronously obtain corrosion evolution data of stress concentration area, and quantitatively weight EET-MIC and H2S-induced hydrogen-induced cracking (HIC), to provide technical support for high-strength steel MISCC risk assessment and targeted protection. SUMMARY
[0004] The application aims to provide a method for regulating microbial stress corrosion cracking.
[0005] The technical scheme of the application is a method for regulating microbial stress corrosion cracking, comprising: a) preparing a U-shaped metal sample, calculating and marking the stress concentration area by using a finite element method; b) keeping the volume of culture medium, strain type and inoculation amount constant, adding solid fillers with gradually increasing specific surface area into a closed anaerobic bottle in sequence to construct a multi-stage biofilm attachment area gradient; c) immersing the U-shaped sample into the bottle after applying a constant tensile stress to the sample, so that the sample surface only contacts the culture medium and the biofilm distribution determined by the fillers, and ensuring that the stress concentration area is opposite to the largest attachment surface; d) culturing at a constant temperature, and regularly detecting the corrosion indicators of the stress concentration area; e) taking out the sample after reaching a predetermined period, observing the crack morphology of the stress concentration area by using a scanning electron microscope, and measuring the crack length and width, and then analyzing the corrosion product composition and relative content in the area by using X-ray photoelectron spectroscopy; f) establishing a “biofilm attachment area-stress concentration area-corrosion mechanism” quantitative correlation framework by comprehensively analyzing the data of steps d) and e), and determining the weight of EET-MIC and HIC. Corrosion rate The quantitative relationship between crack propagation depth and microbial stress corrosion cracking behavior was studied to control the adhesion area.
[0006] Optionally, the solid filler is a sodium-calcium glass sphere with a diameter of 6 mm and 12 mm, which is used in combination to achieve a specific surface area gradient.
[0007] Optionally, by adjusting the diameter 2r and the number n of the soda-lime glass beads, the total specific surface area A=4πr²n of different sealed anaerobic bottles can be made into a multi-level attachable area, while keeping the liquid culture medium and headspace volume constant, so as to eliminate the interference of volume effect on area variables.
[0008] Optionally, the sealed anaerobic bottle forms three levels of attachable area: small, medium, and large.
[0009] Optionally, the constant tensile stress is generated by tightening the bolts at the bottom of the U-shaped specimen, and the stress value is between 60% and 80% of the material's yield strength.
[0010] Optionally, the corrosion indicators periodically detected in step d) include at least one of the following: biofilm cell count, H2S and H2 gas concentration, weight loss, open circuit potential, electrochemical impedance spectroscopy, linear polarization resistance, and potentiodynamic polarization curve.
[0011] Optionally, the predetermined period is 3 days, 7 days, and 14 days, corresponding to the initial stage, active stage, and decline stage of biofilm formation, respectively.
[0012] Optionally, the quantitative relationship is obtained by establishing a mathematical model with the biofilm attachment area as the independent variable and the corrosion rate and crack propagation depth in the stress concentration zone as the dependent variables.
[0013] Optionally, the quantitative relationship established in step f) is used to assess the dual mechanism of microbial stress corrosion cracking: when the biofilm attachment area is small, corrosion is mainly dominated by the extracellular electron transfer (EET) mechanism of sulfate-reducing bacteria, resulting in a high weight loss rate and passivated crack morphology; when the biofilm attachment area is large, the contribution of hydrogen-induced cracking mechanism promoted by hydrogen sulfide (H2S) produced by microbial metabolism in corrosion increases, resulting in sharper and deeper cracks.
[0014] Optionally, the application of the quantitative relationship includes: based on the actual service environment of the target pipeline steel, adjusting the effective area available for biofilm attachment in that environment to be below a critical threshold in order to preferentially suppress the EET mechanism, thereby achieving targeted mitigation of microbial stress corrosion cracking behavior.
[0015] In summary, the method presented in this application, through ingenious design, achieves precise control and quantitative analysis of microbial stress corrosion cracking (MISCC) behavior. By introducing "biofilm adhesion area" as a key control variable, the method systematically reveals the regulatory mechanism of biofilm spatial distribution on crack initiation and propagation. The stress concentration zone is pre-calibrated using finite element analysis and aligned with the maximum adhesion surface, ensuring the accuracy and repeatability of corrosion observation. Experimental results show that this method effectively decouples the dynamic dominant roles of extracellular electron transfer (EET) and metabolites (H2S) in the MISCC process: under small adhesion areas, the EET mechanism dominates early pitting corrosion, while under large adhesion areas, the hydrogen-induced cracking effect of H2S significantly promotes crack tip propagation. The established "biofilm adhesion area"... Corrosion rate The quantitative relationship between crack propagation depth and crack depth provides a direct theoretical basis for predicting material failure risks and formulating targeted protection strategies in industrial environments. Attached Figure Description
[0016] Figure 1 A flowchart of the method for regulating microbial stress corrosion cracking (MISCC) provided by the present invention; Figure 2 The original stress-strain curves and stress distribution cloud diagrams calibrated by finite element analysis are shown for the X80 U-shaped specimen. Figure 3 A schematic diagram of anaerobic bottle packing material for constructing a three-tiered biofilm attachment area of "small-medium-large"; Figure 4 A schematic diagram showing the loading, sealing, and target area exposure methods for the U-shaped sample; Figure 5 The results of viable counts of D. vulgaris on the X80 surface under different adhesion areas (100 / 390 / 640 cm²) are shown in the figure. Figure 6 For the corresponding Figure 5 CLSM fluorescence distribution map of live bacteria (green indicates live cells); Figure 7 The curve of H2 concentration in headspace organisms changing over time; Figure 8 The curve shows the change in H2S concentration in the liquid phase over time. Figure 9 Figures showing the rate of weight loss per unit area under different attachment areas; Figure 10 SEM images of crack morphology in the stress concentration zone section (days 3, 7, and 14); Figure 11 for Figure 10 A schematic model of the mechanism (EET-MIC vs H2S-HIC); Figure 12 The open circuit potential (OCP) timing curves are shown for different attachment areas. Figure 13 For the corresponding Figure 12 Schematic diagram of changes in electron transport path; Figure 14 EIS spectra (Nyquist and Bode) on days 1, 3, 7, and 14. Figure 15 For fitting Figure 14 The equivalent circuit model; Figure 16 This is a time-series trend graph of the linear polarization resistance Rp; Figure 17 The electrokinetic polarization curve is shown on day 14. Figure 18 High-resolution XPS spectrum of Fe 2p corrosion products in the crack zone; Figure 19 A schematic diagram of the synergistic mechanism of "bio-chemical-mechanical" processes in the entire MISCC process. Detailed Implementation
[0017] With the continued growth of global energy demand, the safe transportation of oil and natural gas has become a critical link. Against this backdrop, high-performance pipeline steel, especially X80 steel, is widely used in long-distance pipelines due to its excellent comprehensive mechanical properties and high cost-effectiveness [1-4]. However, pipelines face severe corrosion challenges in complex service environments, especially when buried in soils containing sulfides or with high microbial activity. Among these, microbial corrosion is one of the main threats leading to the degradation of pipeline material performance, shortened service life, and even sudden failure.
[0018] Among the many microorganisms associated with MIC (microbial corrosion), sulfate-reducing bacteria (SRB) are the most common and corrosive group, often identified as the main cause of corrosion failure of pipeline steel in soil environments [7,8]. Under anaerobic conditions, SRB produce hydrogen sulfide (H2S) through their metabolic activities and form a biofilm on the metal surface, thereby triggering a series of electrochemical reactions and localized corrosion processes [9]. Recent studies have shown that SRB-induced MIC not only includes chemical corrosion caused by its metabolic byproducts (such as H2S), but also involves the extracellular electron transfer (EET) pathway. Through the EET mechanism, SRB can directly participate in the process of obtaining electrons from the metal surface, thereby significantly accelerating corrosion.
[0019] When corrosive factors are combined with sustained tensile stress, pipeline steel is highly susceptible to stress corrosion cracking (SCC), which is a major failure mode of X80 steel during service
[12] . The combination of microbial corrosion and mechanical stress leads to more complex microbial-induced stress corrosion cracking (MISCC) behavior [13,14]. The structure, thickness and spatial distribution of SRB biofilm directly affect the accumulation of local corrosion metabolites and the efficiency of electron transfer, thereby changing the electrochemical microenvironment of corrosion sites. Differences in biofilm coverage also affect the growth activity of SRB, H2S release rate and EET behavior. Therefore, a thorough understanding of the SCC behavior and mechanism of X80 steel under different SRB biofilm distributions and stress conditions is crucial for accurately assessing MISCC risk, rationally selecting materials and formulating effective protection strategies.
[0020] While existing research has confirmed the corrosive effect of SRB on steel materials, a systematic experimental study is still lacking on the quantitative relationship between the spatial distribution characteristics of biofilms and their synergistic effect on the corrosion of EET-MIC and metabolic products (H2S), thereby influencing the initiation and propagation morphology of MISCC cracks (such as crack sharpness and depth). In particular, how to simulate different biofilm distributions through controllable experimental methods and directly link them to crack evolution in stress concentration zones is a key problem that needs to be solved.
[0021] See Figure 1 This solution provides a method for controlling microbial stress corrosion cracking, including: a) Prepare U-shaped metal specimens and calculate and calibrate stress concentration areas using the finite element method; The purpose of preparing U-shaped metal specimens is to reproduce, on a laboratory scale, the combined bending and tensile stress state experienced by pipeline steel during actual service.
[0022] First, the sheet metal was CNC wire-cut according to ASTM G30 specifications, ensuring that the tolerances for the length of both arms, the radius of the arc, and the thickness were ≤ 0.05 mm. Then, it was progressively sanded with 600# SiC sandpaper and ultrasonically cleaned to eliminate machining marks and residual scratches, avoiding the introduction of additional stress concentration sources. After geometric machining, a three-dimensional elastic-plastic model was established on the ABAQUS platform: the measured stress-strain curves, Poisson's ratio, and hardening exponent were input. The outer edge of the arc was locally meshed with C3D8R elements to a depth of 0.2 mm. By fixing one end and applying bolt displacement boundary conditions to the other, the maximum von Mises stress of 744 MPa was calculated, located 5 mm from the apex on the outer side of the arc. This high-stress area was defined as the "target area" for subsequent biofilm adhesion, electrochemical testing, and crack observation, ensuring that all corrosion data were collected under the same stress gradient, achieving repeatability and quantifiability of the coupled experiment of "stress concentration—biofilm distribution—crack initiation".
[0023] See Figure 2 Figure a shows the original stress-strain curve of X80 steel. Figure 2 b shows the finite element simulation results of the stress distribution on the surface of the X80 U-shaped bend.
[0024] Figure 2 (a) The original stress-strain curve of X80 steel shows its mechanical behavior during tensile testing. The curve reveals that X80 steel, as a high-strength pipeline steel, exhibits a typical elastic deformation stage, yield plateau, and plastic deformation region. The initial linear portion of the curve represents the elastic deformation stage, with the slope representing Young's modulus. After the yield point, the material enters the plastic deformation stage, exhibiting good ductility. These mechanical properties provide crucial input data for subsequent finite element analysis.
[0025] Figure 2 b is a three-dimensional stress distribution diagram. The red area represents the region of highest stress concentration, mainly concentrated at the top edge of the sample, with a maximum stress value of approximately 744 MPa. This stress level is close to or may exceed the yield strength of the material, making this region most susceptible to microbial-induced stress corrosion cracking.
[0026] b) Keep the culture medium volume, strain type and inoculum constant, and add solid packing material with progressively increasing specific surface area into a sealed anaerobic bottle to construct a multi-level biofilm adhesion area gradient.
[0027] Optionally, the solid filler is a soda-lime glass sphere with a diameter of 6 mm and 12 mm, which are used in combination to achieve a specific surface area gradient.
[0028] Optionally, by adjusting the diameter 2r and the number n of the soda-lime glass beads, the total specific surface area A=4πr²n of different sealed anaerobic bottles can be made into a multi-level attachable area, while keeping the liquid culture medium and headspace volume constant, so as to eliminate the interference of volume effect on area variables.
[0029] Specifically, to eliminate the interference of fluctuations in "nutrient concentration-bacterial count" on the corrosion results, the entire system maintained a fixed culture medium volume (e.g., 100 mL), a fixed Desulfovibrio vulgaris strain, and a fixed inoculation density (e.g., 1 × 10⁻⁶). 6 cells·mL -1 Set as a locked parameter, and introduce variables only by changing the geometric area available for biofilm attachment.
[0030] The sealed anaerobic bottle forms three levels of attachable area: small, medium, and large.
[0031] The specific procedure involves sequentially filling the 50 mL empty volume of a 450 mL serum bottle with sterilized soda-lime glass beads of 6 mm and 12 mm diameters, which have been sterilized at 121 °C, or using a solid epoxy resin block as a "zero-filler" control. The theoretical calculation of the number of glass beads is based on a hexagonal close packing factor of 0.740 to ensure that the liquid phase occupies a consistent porosity, thereby maintaining a constant liquid-gas interface area.
[0032] The first packing scheme yields an adhesion surface of approximately 100 cm² (bottle wall + epoxy resin solid block surface), corresponding to a "small area" gradient. When 55 12 mm glass spheres are added, the spherical surface area increases by 248 cm², raising the total adhesion surface area to 390 cm², forming a "medium area" gradient. Further replacement with 442 6 mm glass spheres doubles the specific surface area to 640 cm², constituting a "large area" gradient. These three levels of area difference (100 → 390 → 640 cm²) create an adhesion area ratio of 1:3.9:6.4 within the same liquid volume, while maintaining consistent liquid flow shear, dissolved oxygen residue, and headspace volume. This allows subsequent observations of corrosion differences to be uniquely attributed to changes in the "spatial distribution of the biofilm," achieving single-factor variable control in the area-mechanism coupling experiment.
[0033] Figure 3 This study demonstrates the design and computational principles of the core experimental setup used to establish different biofilm distributions, and intuitively explains how sulfate-reducing bacteria can be controlled by changing the available attachment area within the anaerobic bottle. Desulfovibrio vulgaris Distribution of biofilms.
[0034] c) After applying a constant tensile stress to the U-shaped sample, immerse it in the bottle so that the sample surface is in contact only with the culture medium and the biofilm distribution determined by the filler, ensuring that the stress concentration area is directly opposite the maximum adhesion surface; To reproduce the original scenario of synergistic damage of pipeline steel due to tensile stress and microbial film during service in the laboratory, a quantifiable and constant tensile load needs to be applied to the U-shaped specimen.
[0035] Constant tensile stress is generated by tightening the bolts at the bottom of the U-shaped specimen, and the stress value is between 60% and 80% of the material's yield strength.
[0036] Specifically, firstly, Φ 6 mm smooth circular holes are machined at symmetrical positions on the sample support. After degreasing with acetone, insulating polyetheretherketone (PEEK) bolts are inserted, and a tightening torque of 25 N·m is applied using a torque wrench. This torque, converted from a pre-calibrated strain gauge-load curve, corresponds to an elastic tensile stress of 0.9 σ_y (approximately 520 MPa) at the outer edge of the arc. This ensures that the stress concentration zone is located at the top of the arc while avoiding overall yielding that could lead to plastic relaxation. The entire fixture and bolts are isolated using PEEK and PTFE bushings to completely cut off the metal-to-metal conductive path, eliminating interference from gap cell or galvanic corrosion on stress corrosion data.
[0037] After loading, the sample was immediately immersed vertically in the culture medium of the anaerobic bottle with the arc facing down and the support legs facing up, following the principle of "stress concentration area facing the maximum adhesion surface": for the 100 cm² system, the distance between the outer edge of the arc and the inner wall of the epoxy was maintained at 5 mm; for the 390 cm² and 640 cm² systems, the distance between the arc and the apex of the innermost glass sphere was also controlled at 5 mm, ensuring that the high-stress area and the thickest area of the biofilm completely overlapped in space. The remaining surface of the sample was sealed with a medical silicone sleeve, exposing only the 1 cm² arc target area, so that the corrosive medium, bacterial extracellular polymers and metabolites could only interact with the tensile metal in this area, thereby achieving precise positioning and repeatable observation of the coupling of "stress-biofilm-crack initiation".
[0038] Figure 4 (a) Schematic diagram of the specimen used in the immersion test, illustrating the treatment method of the X80 U-bend specimen for long-term microbial immersion testing. The bolted area of the specimen was sealed with 3M epoxy resin, leaving only an exposed area of approximately 12 cm² on the outer surface of the bottom of the U-bend, which would be in direct contact with the culture medium containing sulfate-reducing bacteria (D. vulgaris). This design ensures that corrosion and microbial adhesion occur only in the designated study area, while effectively avoiding galvanic corrosion that could occur between the bolts and the specimen. Figure 4(b) Schematic diagram of the sample used for electrochemical testing, illustrating the preparation method of the working electrode for electrochemical testing. Similar to the immersion test sample, most of the sample surface is covered with epoxy resin, but a precise 1 cm² area is designated at the top of the U-bend as the working electrode surface. Furthermore, the schematic diagram clearly shows the copper wire connection points welded to the sample legs, which are used to establish a circuit with the electrochemical workstation. All non-working areas, including the copper wires, bolts, and other parts of the sample, are strictly sealed to ensure the accuracy and reliability of the electrochemical measurements.
[0039] d) Incubate at a constant temperature and periodically monitor corrosion indicators in stress concentration areas; The entire training phase is in (37) ± The culture was carried out in a constant-temperature water bath at 0.5°C to match the optimal growth temperature of *Desulfovibriovulgaris* and ensure stable metabolic activity. Filtered and sterilized N2 (99.999%) was introduced through the top of the water bath to maintain an oxygen partial pressure below 0.1 ppm, ensuring a strictly anaerobic environment. Every 24 hours, 2 mL of culture medium was extracted via a sterile sampling valve and immediately used for pH, oxidation-reduction potential (ORP), and dissolved H2S concentration measurements to ensure the chemical environment remained under control.
[0040] Corrosion indicators that are regularly tested include at least one of the following: biofilm cell count, H2S and H2 gas concentration, weight loss, open circuit potential, electrochemical impedance spectroscopy, linear polarization resistance, and potentiodynamic polarization curve.
[0041] Corrosion monitoring focuses on pre-calibrated stress concentration areas. Specifically, this may include: every 48 hours, a three-electrode system is formed by the working electrode (WE, i.e., the arc segment of the U-shaped sample), the reference electrode (saturated calomel electrode, SCE), and the counter electrode (Pt sheet), connected to a portable electrochemical workstation, and the open circuit potential (OCP, sampling interval 1 s, duration 300 s) and linear polarization resistance (LPR, ±10 mV vs. OCP, scan rate 0.166 mV s) are sequentially measured. -1Electrochemical impedance spectroscopy (EIS, 10 kHz–10 mHz, 5 mV sinusoidal perturbation) was used to obtain charge transfer resistance Rct and polarization resistance Rp. Simultaneously, a micro-pH electrode (100 μm tip diameter) was used to measure the surface pH gradient of the stress concentration zone, and a portable H2S micro-sensor (0.1 ppm resolution) was used to record the H2S concentration at the liquid-film interface. All electrochemical tests were completed within 30 min. Electrode connections were immediately disconnected after data acquisition, and cultivation continued to ensure continuous data time series and to avoid interfering with the natural evolution of the biofilm. Through this integrated "chemical-electrochemical-microenvironment" periodic monitoring, dynamic information on the corrosion initiation, acceleration, and steady-state stages of the stress concentration zone can be captured in real time, providing a basis for subsequent establishment of a "biofilm adhesion area..." Corrosion rate The coupled model of "crack propagation depth" provides quantitative basis.
[0042] e) After the predetermined period is reached, the sample is taken out. First, the crack morphology in the stress concentration area is observed by scanning electron microscopy and the crack length and width are measured. Then, the composition and relative content of corrosion products in the area are analyzed by X-ray photoelectron spectroscopy. The predetermined cycles are 3 days, 7 days, and 14 days, corresponding to the initial stage, active stage, and decline stage of biofilm formation, respectively.
[0043] When the culture reaches the set cycle (3 days, 7 days, or 14 days), the bottle stopper is aseptically opened immediately in an anaerobic chamber. The sample surface is gently rinsed three times with PBS buffer (pH 7.4, containing 0.1% peptone) sterilized at 121 °C to remove loosely attached bacteria and culture medium residue. Then, the sample is immersed in 2.5% glutaraldehyde-0.1 M phosphate fixative at 4 °C for 6 h to complete in-situ fixation of the biofilm. The fixed sample is then dehydrated sequentially with 30%, 50%, 70%, 80%, 90%, and 100% (v / v) ethanol for 10 min at each stage. Finally, the sample is dried at room temperature in hexamethyldisilazane (HMDS) for 15 min to avoid secondary damage to the crack morphology during metallographic preparation.
[0044] After drying, the arc segment of the U-shaped sample was cut into 5 mm × 5 mm observation blocks along the axis of symmetry, ensuring that the cut surface was far from the stress concentration area to prevent the heat-affected zone from altering the crack propagation path. The sample surface was sputtered with gold for 30 seconds (15 mA current, approximately 10 nm thickness) and then placed under a field emission scanning electron microscope (FE-SEM, accelerating voltage 15 kV, working distance 10 mm). A systematic scan of the stress concentration area was performed using secondary electron mode: first, the maximum stress point was located at 200× low magnification, then progressively magnified to 2000×–10000×, acquiring crack opening width, tip curvature radius, and number of branches. Using the SEM's built-in measurement software, lines were drawn along the crack propagation direction, automatically outputting the crack length (μm) and average opening width (μm). Five of the longest cracks for each sample were counted and their average value was taken to ensure data representativeness.
[0045] After morphological observation, the same sample was transferred to an X-ray photoelectron spectroscopy (XPS) analysis chamber. A monochromatic Al Kα source (hν = 1486.6 eV, power 150 W) and a 400 μm beam spot were used to perform a full-spectrum scan (energy 160 eV) and high-resolution fine spectra of Fe 2p, S 2p, and O 1s (energy 20 eV) on the crack tip and surrounding 2 mm × 2 mm region. Charge drift was calibrated using surface contamination carbon C 1s = 284.8 eV. Using Shirley background subtraction and mixed Gauss-Lorentz peak fitting, the relative atomic percentages of species such as FeS, FeS2, Fe2O3, and FeOOH were quantitatively determined. The SEM and XPS data corroborated each other, simultaneously obtaining crack geometry parameters and chemical "fingerprints," which is crucial for establishing the "biofilm adhesion area" in subsequent analysis. Corrosion rate The quantitative model of "crack propagation depth" provides key inputs.
[0046] f) Combine the data from steps d) and e) to establish the "biofilm attachment area". Corrosion rate The quantitative relationship between crack propagation depth and microbial stress corrosion cracking behavior was studied to control the adhesion area.
[0047] Optionally, a mathematical model is established to obtain the quantitative relationship, with the biofilm attachment area as the independent variable and the corrosion rate and crack propagation depth in the stress concentration zone as the dependent variables.
[0048] The established quantitative relationship was used to assess the dual mechanism of microbial stress corrosion cracking: when the biofilm attachment area is small, corrosion is mainly dominated by the extracellular electron transfer (EET) mechanism of sulfate-reducing bacteria, resulting in a high weight loss rate and passivated crack morphology; when the biofilm attachment area is large, the contribution of hydrogen-induced cracking mechanism promoted by hydrogen sulfide (H2S) produced by microbial metabolism in corrosion increases, resulting in sharper and deeper cracks.
[0049] The application of quantitative relationships includes: based on the actual service environment of the target pipeline steel, by adjusting the effective area available for biofilm attachment in that environment to be below the critical threshold, the EET mechanism is preferentially suppressed, thereby achieving targeted mitigation of microbial stress corrosion cracking behavior.
[0050] The time-series electrochemical parameters (R_p, R_ct, H2S concentration, weight loss rate) obtained in step d) were mapped one-to-one with the crack length, opening width, and relative XPS species content obtained in step e). First, the biofilm adhesion area A (cm²) was used as the basis for the mapping. 2 A three-dimensional scatter plot was drawn with the 14-day steady-state corrosion rate v_corr (mm / a) and the maximum crack depth a (μm) as the left and right axes, respectively. The empirical equation a = k·A^α·v_corr^β was obtained using nonlinear surface fitting (Levenberg-Marquardt algorithm), where k, α, and β are fitting constants, and R0... 2 A value ≥0.90 confirms a deterministic mathematical relationship between area and degree of damage.
[0051] Furthermore, using the mechanism contribution as an internal variable, we introduce the EET index (I_EET = 1 / R_ct) and the HIC index (I_HIC = [H2S]·a^(1 / 2)), deconstructing the three-dimensional relationship into a coupling matrix of "area-EET / HIC weight-crack depth": when A < 200 cm 2 When I_EET / I_HIC > 3, the crack exhibits a shallow and wide morphology; when A > 500 cm 2 When I_EET / I_HIC < 0.5, the crack becomes deep and sharp. Using this matrix, the required adhesion area can be calculated by presetting the target crack depth or allowable corrosion rate. This allows for the targeted inhibition or acceleration of microbial stress corrosion cracking behavior through a single geometric parameter, providing a quantitative basis for targeted control of biofilm distribution, optimization of cathodic protection, and coating design in the field.
[0052] This application's method achieves precise regulation and quantitative analysis of microbial stress corrosion cracking (MISCC) behavior. By introducing "biofilm adhesion area" as a key control variable, the method systematically reveals the regulatory mechanism of biofilm spatial distribution on crack initiation and propagation. The stress concentration zone is pre-calibrated using finite element analysis and aligned with the maximum adhesion surface, ensuring the accuracy and repeatability of corrosion observation. Experimental results show that this method effectively decouples the dynamic dominance of extracellular electron transfer (EET) and metabolites (H2S) in the MISCC process: under small adhesion areas, the EET mechanism dominates early pitting corrosion, while under large adhesion areas, the hydrogen-induced cracking effect of H2S significantly promotes crack tip propagation. The established "biofilm adhesion area"... Corrosion rate The quantitative relationship between crack propagation depth and crack depth provides a direct theoretical basis for predicting material failure risks and formulating targeted protection strategies in industrial environments.
[0053] The following description is based on specific experimental results.
[0054] Cell counting analysis: The measurement method is as follows: On days 3, 7, and 14 of culture, the sample is taken out, the surface is rinsed with PBS buffer to remove loosely attached airborne bacteria, the surface is gently brushed with a disposable brush to collect the biofilm, and the biofilm is transferred to PBS solution. After vortexing and mixing, the cells are counted using a hemocytometer under a 400x optical microscope.
[0055] Figure 5 The statistical results of the number of *Desulfovibrio vulgaris* (D. vulgaris) colonies adhering to the surface of X80 U-shaped curved specimens under different biofilm distribution areas (100 cm², 390 cm², and 640 cm²) are presented. The data in the figure show that at the same time point, the highest number of colonies was observed under a biofilm distribution area of 100 cm², and the lowest under 640 cm², indicating that the biofilm is thicker and the bacterial density is higher under smaller distribution areas. The colony count peaked on day 7, and decreased on day 14 due to nutrient depletion. This figure shows that the smaller the biofilm distribution area, the greater the amount of *D. vulgaris* adhering, the stronger the corrosive activity, and thus exacerbate the microbial-induced stress corrosion cracking (MISCC) process.
[0056] Observations using a confocal laser scanning microscope (CLSM): The measurement method was as follows: Samples were taken out on days 3, 7, and 14 of culture. After rinsing the surface with PBS buffer to remove loose bacteria, the samples were stained with LIVE / DEAD® Biofilm Kit fluorescent dye in the dark for 20 min. Z-stack imaging was performed using a Zeiss LSM900 confocal laser scanning microscope (excitation / emission wavelength: 488 / 500–550 nm for live cells, 561 / 600–700 nm for dead cells). Green fluorescent live bacterial spots were counted using ImageJ software. Figure 6 The fluorescence distribution of viable bacteria on the surface of X80 samples is presented under different biofilm distribution areas (100 cm², 390 cm², and 640 cm²). The figure shows that the density of green fluorescent spots is highest in the 100 cm² group and lowest in the 640 cm² group; within the same area, the fluorescence intensity peaks on day 7 and decreases on day 14 due to nutrient depletion. The quantitative fluorescence results are consistent with... Figure 5 The consistent cell count trend visually confirms that a smaller distribution area forms a thicker biofilm with a higher density of viable bacteria, providing a microbiological basis for subsequent EET-MIC acceleration.
[0057] Headspace H2 concentration determination The measurement method is as follows: On days 1, 3, 7, 10, and 14, 10 mL of headspace sample is drawn using a syringe with a sealed valve. If the hydrogen concentration exceeds 1000 ppm (v / v), 250 mL of pre-filled air bag is injected for dilution, and then the sample is measured using a BH-90A portable hydrogen analyzer. The result is converted to the original volume fraction.
[0058] Figure 7 It shows the distribution area of different biofilms (100 cm²) 2 390 cm 2 640 cm 2 The curve showing the change in H2 concentration over time in the headspace of the culture flask under the specified conditions. The data in the figure show that at the same time point, at 640 cm⁻¹... 2 The highest H2 concentration was observed over a 100 cm² area. 2 The lowest values were observed in all groups, with peak values reaching 10 days followed by a decline due to carbon source depletion. This figure indicates that a larger biofilm distribution area, higher total bacterial count, and continuous metabolism result in more accumulated H2, providing an internal hydrogen source and pressure driving force for subsequent hydrogen-induced stress corrosion cracking.
[0059] Determination of dissolved H2S concentration The measurement method and steps are as follows: the headspace H2S concentration is measured simultaneously using a GAXT-H-DL portable H2S detector. If the reading exceeds 100 ppm (v / v), it is diluted before measurement. The liquid phase dissolution [H2S] is calculated based on the gas-liquid equilibrium model proposed by Ning et al.Figure 8 It shows the distribution area of different biofilms (100 cm²) 2 390 cm 2 640 cm 2 Under these conditions, the concentration of dissolved H2S in the culture medium changes over time. The data in the figure show that at 640 cm⁻¹... 2 The dissolved H2S in the group reached its highest level (1.20 × 10⁻⁶) on day 7. -3 M), 100 cm 2 The peak value was lowest in group A; it dropped significantly on day 14 due to nutritional limitations. This figure shows that a larger biofilm distribution area can generate more bio-based H2S, whose dissolved state directly participates in chemical corrosion and hydrogen atom injection, becoming a key chemical driving force for the transformation of cracks from blunt to sharp.
[0060] Weight loss corrosion rate test The measurement method is as follows: On days 3, 7, and 14, the U-bend sample was taken out and ultrasonically cleaned for 10 min with freshly prepared Clarke solution (SnCl2+SbCl3+HCl) to remove corrosion products. After rinsing with deionized water and ethanol, the sample was dried with nitrogen gas and weighed with a 0.01 mg precision balance. The weight loss per unit area was calculated according to ASTM G1-03. Figure 9 It shows the distribution area of different biofilms (100cm²) 2 390 cm 2 640 cm 2 Under these conditions, the weight loss of the X80 sample over time is shown in the figure. The data in the figure show that at 100 cm... 2 The group with the greatest weight loss (3.96 mg cm⁻¹ at 14 days) was [number missing]. -2 ), 640 cm 2 The group with the smallest mass loss was observed; the rate difference was most significant between 1 and 3 days, and narrowed between 7 and 14 days. This figure indicates that high early bacterial count drives EET-MIC, resulting in the fastest mass loss. Later, H2S chemical corrosion contributes more, but the overall weight loss is still positively correlated with the initial bacterial count, providing a material removal basis for the initial pit formation of MISCC.
[0061] Observation of cross-sectional morphology of stress corrosion cracks The measurement method and steps are as follows: U-bend samples were taken on days 3, 7, and 14, washed lightly with PBS, fixed with 2.5% glutaraldehyde at 4 °C for 8 h, dehydrated with ethanol gradient (50–100%), sputter-coated with gold, and the cross-section was observed at 15 kV using a FEI Quanta 250 SEM. The crack length and opening width were measured using ImageJ. Figure 10 It shows the distribution area of different biofilms (100 cm²) 2 390 cm 2 640 cm 2The crack morphology of the X80 specimen cross-section at different times is shown in the figure. Data in the figure shows that at 100 cm... 2 The cracks are short and wide, forming blunt-edged pits; 640 cm 2 The deepest and sharpest cracks were observed on day 14, with a maximum depth of approximately 120 µm. This figure indicates that high bacterial count promotes wide pitting, while high H2S promotes hydrogen-induced sharp cracks, and the two factors work together to determine the morphological evolution and propagation depth of the crack from pit to sharp.
[0062] based on Figure 5 , Figure 7 – Figure 10 The experimental data can be used to create a two-dimensional schematic model using vector graphics software (CorelDRAW + Inkscape). Figure 11 The left side uses red arrows to indicate EET electron flow, and the right side uses blue arrows to indicate H2S diffusion paths; Von Mises stress concentration color scales (red-yellow-green gradient) are added to the pit-crack transformation region, and hydrogen atom penetration is shown in magnified cross-sections at the crack tip; all elements are converted to EMF format and then combined in Word to ensure 600 dpi resolution.
[0063] Figure 11 Divided into two columns, corresponding to two stages. MIC stage: Thick biofilm (high bacterial count, 100 cm²) 2 Fe is transported via outer membrane cytochrome 0 →Fe 2+ +2e - Electrons are transferred through the EET channel, SO4 2- Reduction to generate HS - Localized pH increases, forming wide and shallow corrosion pits; the stress concentration factor at the pit bottom, Kt≈2, has not yet reached the cracking threshold. MISCC stage: Biofilm distribution area increases (640 cm²). 2 This leads to the accumulation of H2S and H2, and the dissolved H2S dissociates into H at the bottom of the pit. + +HS - HS - with Fe 2+ The FeS film is formed by bonding; simultaneously, H atoms are adsorbed (Fe-Hads) and penetrate into the lattice (Fe-Habs), reducing surface energy and bonding strength, and decreasing the stress intensity factor KISCC; under sustained tensile stress of 744 MPa ( Figure 4 At the bottom of the pit, Kt>4, the crack extends sharply along the {110} slip surface, forming a long and narrow transgranular crack. Figure 11 By intuitively integrating the three elements of "biomass-metabolites-mechanical conditions", this study elucidates the dual-mechanism chain of MISCC in which EET-MIC is responsible for pit initiation and H2S-H synergistically drives sharp crack propagation.
[0064] Open circuit potential (OCP) monitoring The measurement method is as follows: At a fixed time each day, the X80 U-bend sample is connected to a three-electrode system (working electrode: U-bend, reference electrode: saturated calomel electrode, counter electrode: Pt sheet), and the open circuit potential (vs. SCE) after stabilization for 300 s is recorded on a VersaSTAT 3F workstation. Figure 12 The figure shows the changes in OCP over time under different biofilm distribution areas (100 cm², 390 cm², and 640 cm²). Data shows that the OCP was consistently the most negative in the 100 cm² group (initially -658 mV, ultimately -638 mV), while it was the most positive in the 640 cm² group (ultimately -521 mV). A sharp negative shift occurred from day 0 to 3, followed by a plateau from day 4 to 7, and then a slow positive shift after slight fluctuations from day 7 to 14. This figure indicates that high bacterial counts lead to increased thermodynamic corrosion tendency, and the negative shift in OCP is synchronous with EET activity and crack initiation, serving as an early electrochemical warning indicator for the SRB-MISCC process.
[0065] Electrochemical impedance spectroscopy (EIS) testing The measurement method steps are as follows: On days 1, 3, 7, 10, and 14, a 5 mV sinusoidal perturbation is applied in the frequency range of 10 kHz–10 mHz, impedance data is collected, and parameters such as Rs, Rf, Rct, and W are extracted by fitting the equivalent circuit according to R(Q(R(Q(RW))) using ZView software. Figure 14 (Nyquist and Bode diagrams) and Figure 15 The equivalent circuit illustrates the impedance evolution under different biofilm distribution areas. Rf decreases with increasing distribution area, while Rct continuously increases over time, and the Warburg impedance W remains significant throughout. This figure shows that biofilm thinning and crack propagation together increase charge transfer resistance, the diffusion process occurs throughout, and the electrochemical impedance can quantitatively reflect the transition of MISCC from microbial to chemical dominance.
[0066] Measurement of linear polarization resistance (Rp) The measurement method is as follows: scan daily at 0.1667 mV / s within the range of ±10 mV vs OCP, and record the slope to obtain Rp. Figure 16 The figure shows the trend of Rp over time. The data indicates that Rp increases linearly over time, reaching its highest value (~900 Ω cm²) in the 640 cm² group, with a steeper upward slope from day 7 to 14, corresponding to the crack propagation stage. This figure demonstrates a positive correlation between Rp and crack length / depth, making it a sensitive indicator for rapid on-site assessment of the severity of SRB-MISCC.
[0067] Potentiodynamic polarization curve The measurement procedure was as follows: on day 14, the corrosion current density icorr and corrosion potential Ecorr were obtained by Tafel extrapolation in the range of -200 to +200 mV vs OCP at 0.1667 mV / s. Figure 17 Polarization curves are shown for different biofilm distribution areas. 100 cm 2 The group with the largest icorr (30.3 µA cm) -2 ), 640 cm 2 The smallest group (7.45 µA cm) -2 Ecorr shifts positively as bacterial count decreases. This figure shows that high bacterial count significantly accelerates anodic dissolution via EET-MIC, and the polarization parameters are highly consistent with weight loss and crack morphology, which can serve as quantitative electrochemical criteria for MISCC activity.
[0068] XPS analysis of corrosion products The measurement method steps are as follows: The sample is taken out on the 14th day, and Ar... + Surface contamination was removed by sputtering to 5 nm, and Fe 2p narrow spectrum was acquired using Thermo K-Alpha X-ray photoelectron spectroscopy and peak fitting was performed using CasaXPS. Figure 18 The peak fractionation results for Fe 2p3 / 2 are presented. The results show that FeS is the main product (712.4 eV, 16.8%), followed by Fe2O3 (710.0 eV) and trace amounts of FeS2 (706.7 eV), with similar compositions across the three product distribution areas. This figure indicates that EET-MIC continuously generates FeS throughout the 14 days, with biogenic H2S providing the sulfur source. The product type is unaffected by the biofilm area, providing a unified phase basis for simulating the electrochemical environment within cracks.
[0069] MISCC mechanism diagram Drawing instructions: Comprehensive Figure 5 – Figure 18 The data was used to create a two-dimensional flowchart in CorelDRAW, which connected electron transfer, H2S generation, FeS deposition and crack propagation in chronological order, and used colors to distinguish microbial (green), chemical (blue) and mechanical (red) processes. Figure 19 Showing D. vulgaris with Fe 0 As an electron donor, SO4 is reduced via EET. 2- Generate HS - , and Fe 2+ The two processes combine to form an FeS film; simultaneously, H2S dissociates, releasing H atoms that penetrate the crystal lattice, promoting the pit-crack transformation under tensile stress, thus realizing a complete MISCC chain involving "biological-chemical-mechanical" synergy. This diagram systematically elucidates the microscopic mechanism of corrosion-cracking in X80 steel driven by SRB, providing a theoretical roadmap for material selection and on-site prevention and control.
[0070] Experimental results show that, during the 0–7 day period, the smaller biofilm distribution area (100 cm²) 2 The highest concentration of *Desulfovibriovulgaris* bacteria was observed, with EET-MIC dominating, leading to the fastest corrosion weight loss, the most negative open-circuit potential, and the lowest polarization resistance, forming wide and blunt corrosion pits. During the 7–14 day stage, these pits formed over a large distribution area (640 cm²). 2 Although the bacterial count decreased, H2 and H2S accumulated at their highest levels, with the dissolved H2S concentration reaching 1.2 × 10⁻⁶. -3 M, the driving crack transforms from blunt to sharp and significantly extends. Corrosion products are predominantly FeS; hydrogen atom penetration and sustained tensile stress jointly promote the pit-crack transformation, with crack depth and charge transfer resistance increasing synchronously. Electrochemical parameters (OCP, Rp, Rct, icorr) are highly consistent with weight loss and crack morphology, indicating that bacterial abundance determines the initial corrosion rate, while the H2S / H2 ratio determines the later crack sharpness; high bacterial abundance and high H2S synergistically produce the longest and deepest cracks. These results not only validate the dual-mechanism model of MISCC coupled with microorganisms (microbes, chemistry, and mechanics) but also provide experimental evidence for in-situ combined electrochemical monitoring and lifetime prediction.
[0071] Finally, it should be noted that the above are merely preferred embodiments of the present invention, used only to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.
Claims
1. A method for controlling microbial stress corrosion cracking, characterized in that, include: a) Prepare U-shaped metal specimens and calculate and calibrate stress concentration areas using the finite element method; b) Keep the culture medium volume, strain type and inoculum constant, and add solid packing material with gradually increasing specific surface area into the sealed anaerobic bottle to construct a multi-level biofilm adhesion area gradient. c) After applying a constant tensile stress to the U-shaped sample, immerse it in the bottle so that the sample surface is in contact only with the culture medium and the biofilm distribution determined by the filler, ensuring that the stress concentration area is directly opposite the maximum adhesion surface; d) Incubate at a constant temperature and periodically monitor corrosion indicators in stress concentration areas; e) After the predetermined period is reached, the sample is taken out. First, the crack morphology in the stress concentration area is observed by scanning electron microscopy and the crack length and width are measured. Then, the composition and relative content of corrosion products in the area are analyzed by X-ray photoelectron spectroscopy. f) Combine the data from steps d) and e) to establish the "biofilm attachment area". Corrosion rate The quantitative relationship between "crack propagation depth" was used to directionally control microbial stress corrosion cracking behavior by regulating the adhesion area.
2. The method according to claim 1, characterized in that, The solid filler consists of soda-lime glass spheres with diameters of 6 mm and 12 mm, which are used in combination to achieve a gradient in specific surface area.
3. The method according to claim 2, characterized in that, By adjusting the diameter 2r and the number n of the soda-lime glass beads, the total specific surface area A=4πr²n of different sealed anaerobic bottles is made into a multi-level attachable area, while the liquid culture medium and headspace volume remain constant, so as to eliminate the interference of volume effect on area variable.
4. The method according to any one of claims 1-3, characterized in that, The sealed anaerobic bottle forms three levels of attachable area: small, medium, and large.
5. The method according to claim 1, characterized in that, The constant tensile stress is generated by tightening the bolts at the bottom of the U-shaped specimen, and the stress value is between 60% and 80% of the material's yield strength.
6. The method according to claim 1, characterized in that, The corrosion indicators that are periodically tested in step d) include at least one of the following: biofilm cell count, H2S and H2 gas concentration, weight loss, open circuit potential, electrochemical impedance spectroscopy, linear polarization resistance, and potentiodynamic polarization curve.
7. The method according to claim 1, characterized in that, The predetermined periods are 3 days, 7 days, and 14 days, corresponding to the initial stage, active stage, and decline stage of biofilm formation, respectively.
8. The method according to claim 1, characterized in that, The quantitative relationship is obtained by establishing a mathematical model with the biofilm adhesion area as the independent variable and the corrosion rate and crack propagation depth in the stress concentration zone as the dependent variables.
9. The method according to any one of claims 1-8, characterized in that, The quantitative relationship established in step f) is used to assess the dual mechanism of microbial stress corrosion cracking: when the biofilm attachment area is small, corrosion is mainly dominated by the extracellular electron transfer (EET) mechanism of sulfate-reducing bacteria, resulting in a high weight loss rate and passivated crack morphology; when the biofilm attachment area is large, the contribution of hydrogen-induced cracking mechanism promoted by hydrogen sulfide (H2S) produced by microbial metabolism in corrosion increases, resulting in sharper and deeper cracks.
10. The method according to claim 8, characterized in that, The application of the quantitative relationship includes: based on the actual service environment of the target pipeline steel, adjusting the effective area available for biofilm attachment in that environment to be below the critical threshold in order to preferentially inhibit the EET mechanism, thereby achieving targeted mitigation of microbial stress corrosion cracking behavior.